2021
DOI: 10.1111/jfb.14909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total dissolved gas supersaturation on the survival of common carp (Cyprinus carpio) and silver carp (Hypophthalmichthys molitrix)

Abstract: Flood discharge results in total dissolved gas (TDG) supersaturation downstream of a dam during the flood period. Fish suffer death from gas bubble disease (GBD) caused by TDG supersaturation. Nonetheless, current studies mainly attach importance to the survival of benthic fish affected by TDG supersaturation in the Yangtze River in China. Few studies have attempted to investigate the survival of pelagic fish influenced by TDG supersaturated water and compare the tolerance characteristics to TDG supersaturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Water supersaturated with total dissolved gasses (TDGs), a state which can be caused by flood outflow from dams, can cause a pathology termed 'gas bubble disease' which can be lethal to carp and other fishes [495,496]. Several studies have been conducted on the effects of TDG supersaturation on various carp species, including grass carp, due to the presence of large dams and declining populations in their native range (Ref.…”
Section: Water Quality Constraints and Effectsmentioning
confidence: 99%
“…Water supersaturated with total dissolved gasses (TDGs), a state which can be caused by flood outflow from dams, can cause a pathology termed 'gas bubble disease' which can be lethal to carp and other fishes [495,496]. Several studies have been conducted on the effects of TDG supersaturation on various carp species, including grass carp, due to the presence of large dams and declining populations in their native range (Ref.…”
Section: Water Quality Constraints and Effectsmentioning
confidence: 99%
“…Subsequently, many studies related to the effects of TDG supersaturation have been carried out. However, most studies have concentrated on the effects of TDG supersaturation on fish tolerance and avoidance behavior (Cao et al, 2015; Deng et al, 2020; Deng et al, 2021; Feng et al, 2019). Studies on the swimming performance of fish subjected to TDG supersaturation are limited.…”
Section: Introductionmentioning
confidence: 99%
“…At 130% and above TDG levels, silver carp (Hypophthalmichthys molitrix) exhibited reduced avoidance behaviour (Ji et al, 2021). The survival rates of sliver carp and common carp decreased when TDG levels rose (Deng et al, 2021). Xue et al (2019) reported that the majority of grass carp (Ctenopharyngodon idellus) died within 90-130 hours when TDG levels were above 127% in an in situ study.…”
Section: Introductionmentioning
confidence: 99%
“…At 130% and above TDG levels, silver carp ( Hypophthalmichthys molitrix ) exhibited reduced avoidance behaviour (Ji et al., 2021). The survival rates of sliver carp and common carp decreased when TDG levels rose (Deng et al., 2021). Xue et al.…”
Section: Introductionmentioning
confidence: 99%